Hubungan Status Gizi dengan Anemia pada Remaja di Kabupaten Bulukumba - Rahmaniyah Rahmaniyah; Ni Luh Gede Sri Wahyudianti; Jusni Jusni (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Anemia is a deficiency in hemoglobin levels in the blood and is a major nutritional problem in Indonesia. The World Health Organization (WHO) in its 2021 world health statistics shows that the prevalence of anemia in women of reproductive age (15-49) in the world in 2019 was around 29.9%. The results of the 2018 Basic Health Research report by Balitbangkes in Indonesia, the prevalence of anemia in young women is around 27.2% in the 15-24 year age group. One of the factors causing anemia is nutritional status. Nutritional status is a factor that is closely related to anemia. This research uses quantitative descriptive, and the research design used in this research is cross sectional. The number of samples used was 10 young women using total sampling techniques. The research was conducted at the Tahirah Al Baeti Bulukumba Midwifery Academy. Adolescents with an inappropriate BMI experienced severe anemia, namely 4 adolescents (80%), 1 respondent (20%) with an inappropriate BMI experienced severe anemia, while 5 respondents (100%) with an appropriate BMI experienced mild anemia. Based on the results of the statistical test p value = 0.004, it can be concluded that there is a significant relationship between nutritional status and the incidence of anemia in adolescents at the Tahirah Al Baeti Bulukumba Midwifery Academy